ABRIGO EFÊMERO: PROPOSTA DE PROJETO DE HABITAÇÃO EMERGENCIAL PÓS DESASTRE - Campos, Alessandro; Leite, Néri Cleyton da Silva (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Disasters resulting from natural phenomena have been frequent in recent years, where the numbers of people affected have been unprecedented, with victims and economic losses. The problems in Brazil, are visible due to the country scenario, with few resources for such a situation. In this way, this work proposes an emergency shelter, adapted to the local characteristics when developing a project appropriate to the basic needs of a shelter, that is economic, easy to transport and that serves the different regions of Brazil. Because it is modular, the sizes fit the people who will occupy each shelter, being able to accommodate from two 02 people in the initial module up to 12 people in the adjacent modules. When proposing a embryo cell with two modules, being 01 bathroom / laundry module, with 4.50m² and 01 mixed module with 9m², this embryo cell will be an adjustable multifunctional space, offering environments for personal hygiene and washing needs in general, and environments for preparing meals in conjunction with living space that can be transformed into a dormitory. The purpose of this study is to create a quickly assembled and flexible housing to meet the needs of the homeless or at risk.